OPTIMASI PRODUKSI ANTIBAKTERI CAIRAN KULTUR ISOLAT BAKTERI (ISOLAT Te234) TERHADAP BAKTERI Escherichia coli DAN Staphylococcus aureus - Sandi Kurniawan; Alfian Syarifuddin; Herma Fanani Agusta; Missya Putri Kurnia Pradani (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2020)
Antibiotics are metabolic products produced by certain microorganisms that can also damage other microorganisms. About 22,000 secondary metabolites in the form of antibiotics are produced by microbes, 70% are produced by actinomycetes, 20% by fungi, 7% Bacillus spp. and 1–2% by other bacteria. This research was conducted to determine the optimal time for bacteria to produce antibacterial which can inhibit the growth of Staphylococcus aureus and Escherichia coli. The method used is the well method with a diameter of 6.00 mm wellbore. The test results obtained, isolates of Te234 can produce optimal antibacterial which can inhibit the growth of Staphyloccus aureus bacteria on the 13th day with inhibition zone diameter of 16.00 ± 4.00mm against Escherichia coli bacteria on the 14th day with inhibitory zone diameter of 15, 33 ± 1.15mm so that it can be used as a determinant of the incubation time to produce antibacterial compounds. The TE 234 isolates are able to produce antibiotics that have the potential for the Staphylococcus aureus bacteria optimally on the 13th day, while on Escherichia coli on the 14th day